Analisis Naratif Lovecraftian Horror dalam Cerita Manga Berserk - Alfath Marzuki; Suluh Gembyeng Ciptadi (Kiwari, 2023)
Manga is a type of media in the form of text and images that can be studied in communication science using a text analysis approach. One type of manga that has a major influence on manga culture is berserk. Howard Philips Lovecraft's work called lovecraftian became a style of horror writing in literature and became one of the most influential genres in manga culture. The purpose of this research is to describe the lovecraftian horror narrative in Berserk manga by using Todorov's narrative level which consists of equilibrium, disruption, recognizing the disruption, attempt to repair damage, and new equilibrium to see lovecraftian horror elements consisting of sense of dread, the existence of the unfathomable, and human feelings as insignificant living beings. This study uses a qualitative approach. The unit of analysis is the Berserk manga chapters 3 – 8, 18 – 21, 89 – 105. The data collection technique is carried out by studying documents consisting of books or scientific journal articles related to research, and documentation in the form of Berserk manga screenshots. The results of the study show that the Berserk manga has lovecraftian horror elements consisting of a sense of dread, the existence of the unfathomable, and human feelings as insignificant living beings. Manga adalah salah satu produk media berupa teks dan juga gambar yang dapat diteliti dalam ilmu komunikasi dengan menggunakan pendekatan analisis teks. Salah satu jenis manga yang memiliki pengaruh besar dalam kultur manga adalah berserk. Karya Howard Philips Lovecraft yang disebut lovecraftian menjadi gaya penulisan horror dalam literatur dan menjadi salah satu genre yang berpengaruh dalam kultur manga. Tujuan penelitian ini adalah untuk mendeskripsikan narasi lovecraftian horror dalam manga Berserk dengan menggunakan tingkatan naratif Todorov yang terdiri atas equilibrium, disruption, recognizing the disruption, attempt to repair damage, dan new equilibrium untuk melihat elemen lovecraftian horror yang terdiri dari sense of dread, the existence of the unfathomable, dan perasaan manusia sebagai makhluk hidup yang insignifikan. Penelitian ini menggunakan pendekatan kualitatif. Adapun unit analisisnya adalah manga Berserk chapter 3 – 8, 18 – 21, 89 - 105. Teknik pengambilan data dilakukan dengan studi dokumen yang terdiri dari buku atau artikel jurnal ilmiah yang terkait dengan penelitian, dan dokumentasi berupa screenshot manga Berserk. Hasil penelitian menunjukkan bahwa manga Berserk memiliki elemen lovecraftian horror yang terdiri dari sense of dread, the existence of the unfathomable, dan perasaan manusia sebagai makhluk hidup yang insignifikan.